Presentation: Colonial Christianity - Allpanchis, Revista (1982)
In Peru, still, the history of Christianity persists as the history of an institution: the Church. It was the path followed in the past by researchers such as Rubén Vargas Ugarte S.J. when studying the cult of Mary, the Lima Councils, the religious orders... But it happens that just as important as knowing the norm is to inquire into the daily practice of a religion, approaching men who, with their beliefs, orthodox or heretical, support the cult. It is the old distinction between the history of religion (of ideas in the abstract) and the history of religiosity. In this issue of Allpanchis we would like to focus on this last aspect, until now quite neglected in historical approaches.